Lycopene Improves the Metformin Effects on Blood Glucose and Neutrophil Counts in Type 2 Diabetic Rats - Medina Sianturi; Neni Susilaningsih; Heri Nugroho; Maria Suryani (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2023)
In patients with type 2 diabetes mellitus (T2DM), both innate and acquired immunity are weakened by hyperglycemia. Lycopene is one of the hydrocarbon carotenoids that has been widely studied for its powerful antioxidant and anti-inflammatory properties, furthermore act as hypoglycemic and immunomodulator. Herein, we investigated the effect of lycopene and metformin combination on fasting blood glucose (FBG) and neutrophil counts. The rats were divided randomly into six groups, each containing five rats. Group 1 consisted of normal rats (N) and group 2, T2DM (DM) rats, which were administered 0.5 mL of coconut oil; group 3 T2DM rats were administered 250 mg/kg of metformin in 0.5 mL of coconut oil; groups  4,5 and 6 rats were administered a combination of metformin 250 mg/kg with 10 mg/kg (DML-10), 20 mg/kg (DML-20) and 40 mg/kg (DML-40) of lycopene in 0.5 mL of coconut oil, respectively. Treatment was administered every day for 28 days. A model of T2DM rats was induced by a high-fat diet for two weeks combined with streptozotocin–nicotinamide. Data were analyzed with a one-way ANOVA test followed by the least significant difference (LSD) test. There were significant differences in FBG levels and the number of neutrophils in all groups. Lycopene combined with metformin had lower FBG concentrations and higher neutrophil counts compared to metformin monotherapy (p<0.001), and these observations were dose-dependent. Lycopene combined with metformin can improve blood glucose and neutrophil counts in rats with diabetes. The highest effect was observed in combination with lycopene at a dose of 40 mg/kg and metformin at a dose of 250 mg/kg.